ANALISIS PENGARUH DIGITAL MARKETING TERHADAP PENINGKATAN KESADARAN MASYARAKAT TERHADAP PRODUK BLUE ECONOMY DI WILAYAH PESISIR SUMATERA UTARA - Welly Arifin, Indra; Handayani Harahap, Hastuti; Rudy Sentosa Rajagukguk, Frederick (Penerbit Lafadz Jaya, 2025)
This study aims to analyze the influence of Digital Marketing on Public Awareness and the development of Blue Economy Products. A quantitative approach was applied using Partial Least Squares Structural Equation Modeling (PLS-SEM) for data analysis. The results indicate that Digital Marketing has a significant direct effect on public awareness (T = 22.284; P = 0.000) and on Blue Economy products (T = 9.004; P = 0.000). However, public awareness does not directly affect Blue Economy products significantly (T = 0.105; P = 0.917). Nevertheless, there is a significant indirect effect of Digital Marketing on Blue Economy products through public awareness (T = 3.098; P = 0.002). These findings highlight the importance of integrated and educational digital marketing strategies in enhancing community engagement and advancing the development of the blue economy sector.